2015
DOI: 10.4103/0973-1296.157707
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid profile, antioxidant and cytotoxic activity of different extracts from Algerian Rhamnus alaternus L. bark

Abstract: Background:Rhamnus alaternus (Rhamnaceae) L. has been traditionally used for treatment of many diseases.Objective:In this study, we determined the antioxidant/free radical scavenger properties, the flavonoid profile and the cytotoxicity of aqueous and methanolic extracts obtained by maceration from Algerian R. alaternus bark, like also of aqueous extract prepared by decoction according to the traditional method. This to estimate the usefulness of the drug traditional preparation and compare it with those made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…Based on the IC50 value of compounds 2 showed stronger activity, suggesting that the presence of an additional hydroxyl group at C-14 and opening of D-ring of triterpenoid structure seems to increase the cytotoxic activity. These results are similar to those of previously reported that the presence of additional of the hydroxyl group and the opening of D-ring in flavonoid structure can increase the cytotoxic activity (Boussahel et al, 2015).…”
Section: Figure 2 1 H-1 H and Hmbc Correlation Of 1 Andsupporting
confidence: 92%
“…Based on the IC50 value of compounds 2 showed stronger activity, suggesting that the presence of an additional hydroxyl group at C-14 and opening of D-ring of triterpenoid structure seems to increase the cytotoxic activity. These results are similar to those of previously reported that the presence of additional of the hydroxyl group and the opening of D-ring in flavonoid structure can increase the cytotoxic activity (Boussahel et al, 2015).…”
Section: Figure 2 1 H-1 H and Hmbc Correlation Of 1 Andsupporting
confidence: 92%
“…While ORAC and Folin–Ciocalteu tests are not suitable for measuring liposoluble antioxidants, ABTS can measure the activity of both water-soluble antioxidants and liposoluble ones and DPPH in turn is soluble only in organic solvents [27, 28]. …”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] and adapted in our laboratory. [ 20 ] This assay is based on the effect of peroxyl radicals generated from the thermal decomposition of 2,2'-azobis (2-methylpropionamidine) dihydrochloride (AAPH) on the signal intensity from the fluorescent probe FL in the presence of an oxygen radical absorbing substance. The reaction was carried out in 75 mM phosphate buffer (pH 7.4), and the final reaction mixture was 2 ml.…”
Section: Methodsmentioning
confidence: 99%